Genes, Gastronomy and Gratitude : The development and future of the conservation of native breeds - Ovaska, Ulla
Acta Electronica Universitatis Tamperensis nr. 1816 The number of native breeds has diminished globally during the last decades. Many breeds have already become endangered or even extinct. The loss of native breeds is still continuing, which will ultimately lead to a global loss of their genetic resources (AnGR) and thereby a loss of agrobiodiversity. The modernisation of agriculture with new technologies and breeds has especially contributed to the situation in which native farm animals have been replaced by better-yielding breeds. Yet, there are multiple reasons to conserve breeds. Many are adapted to difficult climate conditions, and therefore play an important part in answering to future environmental challenges, such as climate change. In addition to their role in sustainable agriculture, there are other reasons to conserve native breeds including, e.g., their role in the landscape, cultural history and rural livelihoods. This research examines the development and future of the conservation of native breeds in two case studies: the conservation of the Yakutian Cattle in the Sakha Republic in the Russian Federation and the conservation of native breeds in Finland. The main research questions examine: how the need for conservation and its meanings have changed over time and what landmarks can be identified; how different actors have argued for the need for conservation, how discourses have developed and what kinds of coalitions have been formed; and how different arguments are translated into policies and policy-making and how the conservation is organised. The research setting comprises: 1) environmental governance dealing with institutions, actors and contents involved with agro-environmental policies, 2) ecosystem services about the benefits ecosystems produce for the well-being of humans and the values underlying these services, and 3) an institutional approach which contributes to understanding the realisation of policies in practice. These approaches provide three complementary perspectives on ...